Identification and modelling of a quadrotor - Lin, Calvin Shenghuai. (2011)
This project involves the modelling and identification of a quadrotor, the X600D. The model developed captures the key dynamics of the quadrotor to estimate the response to a known input. The model can be applied when evaluating model-based control strategy.